2011
DOI: 10.2741/214
|View full text |Cite
|
Sign up to set email alerts
|

P2 receptor expression, signaling and function in osteoclasts

Abstract: Skeletal development and bone remodeling depend on the coordinated activity of osteoblasts and osteoclasts, which are responsible for bone formation and resorption, respectively. Mature osteoclasts result from the fusion of precursor cells, and they are large, multinucleated, highly specialized cells. Cellular release of ATP and UTP occurs in response to a variety of stimuli including mechanical stimulation, which occurs in the bone environment. ATP and UTP or their metabolites can then act on P2 receptors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…Although a number of different P2Y receptors are functionally expressed in osteoclasts, it has been suggested that more P2Y receptors will play a role in osteoclast biology (Reyes et al, 2011). Moreover, whether the RANKL signal regulates expression of P2Y receptor has not yet reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of different P2Y receptors are functionally expressed in osteoclasts, it has been suggested that more P2Y receptors will play a role in osteoclast biology (Reyes et al, 2011). Moreover, whether the RANKL signal regulates expression of P2Y receptor has not yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…Based on studies showing that nucleotides are released in bone in response to mechanical stimuli (Reyes et al, 2011;Wiebe et al, 1999), we examined transcriptional responses of known seven P2Y nucleotide receptors upon RANKL stimulation. As shown in Fig.…”
Section: P2y14 Was Selectively Induced During Osteoclastogenesis Uponmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoclasts, the bone-resorbing cells also express most P2 receptors [14] and respond to extracellular nucleotides with elevation of intracellular calcium [15]. Moreover, extracellular ATP, ADP and UDP have been shown to increase the formation and resorptive activity of primary rodent osteoclasts in vitro [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the role of ATP in bone metabolism [1,2] has been revealed to some extent and quite a few papers have been published in this respect, functions of its metabolite adenosine are not understood. Bone remodelling is a continuous, life-long process that maintains skeletal integrity.…”
mentioning
confidence: 99%